Psychological distress and marital satisfaction among the spouses of patients with alcohol dependence syndrome attending Patan Hospital - Shrestha, Sneha (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Alcohol dependence is considered as an ongoing stressor for individual and family. Among them, spouses are primarily affected because of intimate nature of their relationship. Spouses play an important role in treatment programs related to alcohol and thus there is a need to study psychological distress and marital satisfaction in order to understand and address such issues. Thus, this study aims to identify prevalence of psychological distress and marital satisfaction among spouses of ADS patients.Method: This was cross-sectional study was conducted at Patan Hospital in Nepal. A total of 92 spouses of patient with alcohol dependence syndrome were selected by purposive sampling were assessed using self-administered questionnaire. Psychological Distress and Marital Satisfaction was assessed using DASS 21 and Marital Satisfaction Scale respectively. The descriptive statistics was calculated for socio demographic and association and correlation between marital satisfaction status and psychological distress was done using chi square test and Spearman’s rank correlation coefficient respectively.Result: Majority of respondents had anxiety 59(64.13%) followed by depression 52(56.52%) and 19(20.65%) perceived stress. There was significant association between the psychological distress (Depression, Anxiety and Stress) and marital dissatisfaction in spouses (p-value =